PERBANDINGAN KEKUATAN TEKAN SEJAJAR SERAT TERHADAP KEKUATAN TEKAN TEGAK LURUS SERAT PADA KAYU MAHONI (SWIETENIA MAHAGONI) - Astuti Masdar (Universitas Pendidikan Nasional, 2018)
The information about the behavior of the material is indispensable as the decision onconstruction material to produce a design that is strength, economical and have a serviceability limitstate requirements. In the construction that using natural materials such as timber, loading positionto the fiber of wood greatly influence the behavior of the material. In granting the compressive force,the material receives a compressive force parallel to the fiber will have different behavior withmaterial that receives the compressive force perpendicular fiber of wood. In this research, testing ofcompressive strength have been done on Swietenia Mahagoni. The standard test used is the standardASTM D143-2002: Standard Test Methods for Small Clear Specimens of Timber: Annual Book ofASTM standard 4:10 Vol. The test results showed that the average compressive strength parallel andperpendicular fibers each fiber is 26.76 MPa and 12.37 MPa, so as it can be concluded that thecomparison of the compressive strength of parallel fibers and perpendicular fiber is 1: 0.46 orcompressive forces of perpendicular fibers on the mahogany approximately half of the compressivestrength parallel to the fiber. This can be taken into consideration in the design process on timberconstruction.